Diagnostic Value of Enhanced Computed Tomography and Magnetic Resonance Imaging in Intracranial Infections after Craniocerebral Surgery - Su, Wen; Luo, Honghui; Xu, Lieyin; Cheng, Ge; Li, Xiaotian; Lin, Bin; Zhou, Zhipeng (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
This study investigated the diagnostic value of enhanced computed tomography (CT) and magnetic resonance imaging (MRI) in postoperative intracranial infections in patients undergoing craniocerebral surgery.A total of 130 patients suspected of developing intracranial infection after cranial surgery were included in the study. All patients underwent MRI and CT examinations. The results of cerebrospinal fluid (CSF) culture were observed. The diagnostic efficacy of CT and MRI for intracranial infections was compared. In addition, univariate and multivariate logistic regression analyses were conducted to identify the factors influencing intracranial infections after surgery.By CSF culture, 45 intracranial infections were finally diagnosed in 130 patients with suspected intracranial infections, including 20 cases of Staphylococcus aureus infections (44.44%), 14 cases of Staphylococcus haemolyticus infections (31.11%), and 11 cases of Staphylococcus epidermidis infections (24.44%). The sensitivity, specificity, and accuracy of CT in diagnosing intracranial infections were 51.11, 89.41, and 76.15%, respectively. In comparison, MRI demonstrated a sensitivity of 77.78%, specificity of 92.94%, and accuracy of 87.69% in diagnosing intracranial infections. Logistic multifactorial regression analysis showed that surgical approach, surgical time, CSF leakage, and ventricular drainage were independent risk factors of postoperative intracranial infections (odds ratio > 1, p < 0.05).MRI has a higher diagnostic accuracy for intracranial infections compared with CT. Various factors contribute to the development of intracranial infections following cranial surgery, which warrants careful attention and timely targeted interventions to reduce the risk of such infections.
Keywords: magnetic resonance imaging; computed tomography; risk factors; craniocerebral surgery; postoperative infection